Dynamics of the Capital Structure of Multinational Subsidiaries in Emerging Markets : A Literature Review on the Role of Internal Capital Markets and Institutional Risks - Geby Citra Ananda; Khaira Amalia Fachrudin (Yayasan Multidimensi Kreatif, 2026)
This study aims to synthesize the latest literature on the determinants of the capital structure of Multinational Corporation (MNC) subsidiaries in emerging markets. The primary focus is on the efficiency of the Internal Capital Market (ICM) and the moderating influence of institutional risk. By reviewing research from the past five years, this article identifies a shifting trend in which financial digitalization and global geopolitical uncertainty reinforce the role of the ICM as a liquidity buffer. This article also highlights how the quality of local institutions in emerging markets determines the choice between internal and external debt as a risk mitigation strategy.